Higher Education and Science in Brazil: A Walk toward the Cliff? - Knobel, Marcelo; Leal, Fernanda (International Higher Education, 2019)
The recent declarations and measures enacted by President Jair Bolsonaro in regard to Brazilian higher education and science have caused great concern and created considerable confusion. This article summarizes the main events taking place since January 2019, as well as their possible implications for the future. Given the importance of public universities and federally funded public agencies for the country’s social and economic demands, budget cuts and hostility toward academic institutions effectively “cut the government’s own throat.”